STUDENTS’ DEVELOPMENT AND SUCCESS IN UNIVERSITY: INSIGHTS FROM PILAH THE EXPLORER PROGRAMME - Md Rashid, Siti Nafisah; Jaafar, Nor Fadhlin; Hashim, Norshida; Almuddin, Syahirah; Abdul Aziz, Nurulnabilah (Journal of Islamic, Social, Economics and Development, 2024)
Student associations play a vital role in fostering a vibrant and inclusive campus environment while promoting the holistic development of students. The success of a university student is not solely determined by their academic performance; it also encompasses their involvement in extracurricular activities. This study evaluated students’ achievement by engaging them as members of the organising committee throughout the development and implementation of the Pilah the Explorer programme. The programme was organised by Kelab Sahabat, in partnership with three other student clubs, namely Persatuan Bahasa Arab, Filmex Photo Vision, and Textile Society of Applied Science (TEXSAS). This programme involved the management of a treasure hunt activity consisting of 8 checkpoints around UiTM Kuala Pilah with activities designed to enhance the participants' cognitive capacities and critical thinking skills. A survey was given to a group of 42 students who served as committee members. The survey included 5-point Likert scale questions and 1 open-ended question to gather their input on the management of this programme. From their responses, the majority of the committee members believed that this activity enhances their interpersonal capabilities, including their capacities for communication, leadership, social skills, collaboration, and the formation of collaborative networks with their peers.